2021
DOI: 10.1016/j.jstrokecerebrovasdis.2021.105953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Stroke Severity and Mortality in the South-East of Santiago, Chile

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The included articles were composed of 46 retrospective studies (cohort (n=7); observational (n=11); cross-sectional (n=3); archive (n=1); review (n=1); unspecified (n=23)); 10 prospective studies (cohort (n=2); observational (n=3); cross-sectional (n=3); unspecified (n=2)); 26 observational studies (reports (n=9); cohort (n=7); cross-sectional (n=1); unspecified (n=9)); one matched pairs study; and one survey and one exploratory design. The included articles demonstrated wide geographical spread spanning Bangladesh 29 ; Canada 3032; Chile 33 ; China 15,3437,3744; Egypt 45 ; Finland 46 ; France 47 ; Germany 4850; India 51 ; Iran 52,53 ; Israel 5456; Italy 8,5767; Japan 9,68 ; Lithuania 69 ; Malaysia 70 ; Netherlands 71 ; Norway 72,73 ; Saudi Arabia 74,75 ; Spain 7679; Switzerland 80 ; Taiwan 81 ; United Kingdom 8284; and United States of America 7,20,24,39,85104 . The studies encompassed participants from a wide range of diverse backgrounds, including individuals from various racial and ethnic communities, linguistic minorities, and persons with differing levels of disability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included articles were composed of 46 retrospective studies (cohort (n=7); observational (n=11); cross-sectional (n=3); archive (n=1); review (n=1); unspecified (n=23)); 10 prospective studies (cohort (n=2); observational (n=3); cross-sectional (n=3); unspecified (n=2)); 26 observational studies (reports (n=9); cohort (n=7); cross-sectional (n=1); unspecified (n=9)); one matched pairs study; and one survey and one exploratory design. The included articles demonstrated wide geographical spread spanning Bangladesh 29 ; Canada 3032; Chile 33 ; China 15,3437,3744; Egypt 45 ; Finland 46 ; France 47 ; Germany 4850; India 51 ; Iran 52,53 ; Israel 5456; Italy 8,5767; Japan 9,68 ; Lithuania 69 ; Malaysia 70 ; Netherlands 71 ; Norway 72,73 ; Saudi Arabia 74,75 ; Spain 7679; Switzerland 80 ; Taiwan 81 ; United Kingdom 8284; and United States of America 7,20,24,39,85104 . The studies encompassed participants from a wide range of diverse backgrounds, including individuals from various racial and ethnic communities, linguistic minorities, and persons with differing levels of disability.…”
Section: Resultsmentioning
confidence: 99%
“…Despite discussions about the preservation and, in some cases, improvement in stroke care quality during the pandemic 20,81,82 , challenges and disruptions in outpatient care, rehabilitation, and follow-up care were noted in several articles 6,7,30,62,65,66 . Furthermore, studies indicated that patients treated during the pandemic had worse discharge outcomes and increased mortality rates 20,33,85 . Regrettably, higher rates of in-hospital death and hospice discharges were observed during the pandemic period, attributed to longer treatment delays 16,26,79,87 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several countries the impact of COVID-19 pandemic on stroke was seen as an initial decline in the overall number cases and in MT eligible patients, and there were no differences in outcomes or results of advanced treatment [ 3 , 7 , 8 , 9 , 23 , 24 ] Nevertheless, this does not seem to be the reality in lower to middle income countries, especially in South America, like Brazil and Chile, where there is a paucity of data available 25 , 26 , 27 , 28 . Although our differences in 90-day mortality and dependency were not statistically different, there was a trend for worse outcomes and higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…At the peak of the pandemic, a drop in notifications to emergency call centers for life-threatening diseases was observed, with a significant decrease in incidents attended by the emergency medical services (EMS) and the emergency department (ED) ( 2 ). A marked decrease in cases of acute myocardial infarction, stroke, or traffic accidents has also been reported ( 3 5 ), prioritizing COVID-19 ( 2 ). EMS were called upon to respond to biohazard medical emergencies, monopolizing patients with COVID-19 and virtually all ambulance transfers.…”
Section: Introductionmentioning
confidence: 99%